GAYA KEPEMIMPINAN DAN KOMPETENSI DALAM MEMPENGARUHI MOTIVASI KERJA SERTA DAMPAKNYA PADA KINERJA PEGAWAI BIRO UMUM SEKRETARIAT PRESIDEN - Irul, Mudzakir (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
This study aims to analyze and identify the influence of leadership style, competence and work motivation on employee performance with work motivation as an intervening variable at the General Bureau of the Presidential Secretariat.Sampling was carried out through the distribution of questionnaires by a Likert scale with one of the non-probability sampling techniques, namely saturated sampling to 70 employees. The data analysis method uses path analysis by the SPSS application.He results of the study consist of 2 sub-structures. Sub-structure I shows that leadership style has a significant effect on work motivation, competence has a significant effect on motivation. Sub-structure II shows that leadership style has a significant effect on employee performance, competence has a significant effect on employee performance, motivation has a significant effect on employee performance, and leadership style, competence and work motivation have a significant effect on employee performance simultaneously.